Efektivitas Senyawa Bioaktif Biji Kopi Arabika (Coffea arabica L.) Sebagai Antibakteri - Sari, Nurmala; Razali, Mariany; Kusuma, Ariyanti; Simanjuntak, Labora; Damanik, Mia; Silvany, Rika (Journal of Pharmaceutical and Health Research, 2024)
Arabica coffee has a myriad of benefits for the health of the human body, Arabica coffee contains secondary metabolites including flavonoids, tannins and saponins which have good antibacterial properties in leaves, seeds, and even coffee fruit skin, where Arabica coffee is taken in a mature state to see how much antibacterial is contained in coffee beans. The purpose of this study was to identify the chemical content of secondary metabolites contained in the ethanol extract of Arabica coffee beans and the antibacterial activity of the extract in terms of preventing the growth of Staphylococcus aureus and Escherichia coli bacteria. This research method is experimental, plant material is taken identified then made simplisia, Arabica coffee beans are extracted using ethanol p.a. solvent, phytochemical screening and antibacterial activity tests are carried out using the agar well diffusion method (Agar Well Plate Diffusion Assay Method). The diameter of the growth inhibition of microorganisms is one of the factors observed in the ethanol extract of Arabica coffee beans undergoing phytochemical screening which shows the presence of terpenoids / steroids, alkaloids, flavonoids, tannins and saponins. The concentrations used start from 100 mg / ml, 50 mg / ml, 25 mg / ml, 12.5 mg / ml, 6.25 mg / ml and 3.12 mg / ml in the ethanol extract of Arabica coffee beans (Coffea arabica L.). The ethanol extract of Arabica coffee beans showed antibacterial activity against Escherichia coli bacteria with the largest inhibition zone of 9.5 mm in diameter observed at a concentration of 100 mg/ml, while the smallest inhibition zone of 0.73 mm in diameter was observed at a concentration of 6.25 mg/ml, in contrast to Staphylococcus aureus bacteria which had the smallest inhibition zone at a concentration of 100 mg/ml and the largest inhibition zone at a concentration of 8.48 mm at 12.5 mg/ml with an inhibition zone diameter of 1.73 mm.